Efectos de la técnica Foam Roller en deportistas con contracturas isquiotibiales - Cedeño Zambrano, Fátima Fabiola (2023)
ABSTRACT: The research work is of documentary type, through a bibliographic review, where the effects of the Foam Roller Technique in athletes with hamstring contractures are verified, making effective the importance of this technique or as an alternative method for the rehabilitation of this pathology. Muscle contractures is a musculoskeletal pathology caused by different factors that prevent the professional or recreational athlete from continuing with his activities; physiotherapy helps the recovery of the athlete and one of these is the proposed therapy, which provides the patient with an effective recovery from the functional limitations caused by the disease. Information was selected from different databases such as: PEDro, PubMed, SciencieDirect, Elsevier, Google Scholar, among others; where 60 articles were found of which 35 scientific articles published worldwide were selected for this research and were verified with the Physiotherapy Evidence Database (PEDro) scale for their methodological validation. The research of the current studies shows that the physiotherapeutic intervention of the Foam Roller technique significantly increases the range of motion (ROM), reduces the sensation of pain and the levels of tension associated with hamstring contractures in athletes, facilitating the reinsertion to competitive or athletic activities.